Community public health practicum in the Amazon region of Peru: Student experiences. Issue 1 (2nd January 2018) - León-Montoya, Gladys; Albar, María-Jesús; León-Larios, Fátima
ABSTRACT: This article presents the experience of a community public health practicum in the Amazon region of Peru. The intervention model is based on the social determinants of health within a participatory approach illustrating the impact of the practicum on the students and on the families and communities. This experience can be instructive for developing countries that do not have an established infrastructure to ensure healthcare within their communities; in these countries, students can help to improve health by empowering families and communities. This paper describes the experience of two students who participated in the community practicum providing healthcare to families and communities.